VARIETY OF ORNAMENTS IN THE MANUSCRIPT OF SHIRATHAL MUSTAQIM BY NURUDDIN AR-RANIRY IN ACEH - Khaizir Imran; Nurdin AR (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
The goal of this research is to determine the historical significance of the Shirathal Mustaqim text as well as the forms of decorating found inside it. A qualitative research technique with a kind of research methodology was employed in this study, which included library research, observation, documentation, primary and secondary data sources, and content analysis. The information gathered in the field was examined to determine that the themes of each design in the Shirathal Mustaqim text that had been investigated had various similarities and differences. The Shirathal Mustaqim script has a variety of flower ornaments, such as bungong pucok rebung, bungong awan-awan, bungong seuleupo, bungong meulu bruk, bungong puta taloe dua, bungong sagoe, bungong glima, bunga bertabur-tebar, kuncup bunga, and bunga ayu-ayu.